(untitled) (International Journal of Management Analytics (IJMA), 2024)
This study investigates the impact of Good Corporate Governance (GCG) components—independent commissioners, institutional ownership, managerial ownership, and audit committees—on the financial performance of banking subsector companies listed on the Indonesia Stock Exchange from 2018 to 2023. Using quantitative analysis of secondary data, the findings reveal that independent commissioners positively influence financial performance, while both institutional and managerial ownership negatively affect it. Conversely, the audit committee does not significantly impact financial performance. The study highlights the importance of governance structures in enhancing financial outcomes and recommends focusing on board composition and ownership structures for improved performance.